The impact of Artficial Intelligence and how it is shaping banking - Joseph Theuri; John Olukuru (Kenya Bankers Association (KBA), 2022)
The importance and adoption of Artificial Intelligence schemes in supporting business operations in risk management and spurring revenue growth continues to gain traction globally. While this has been exacerbated by the disruptions caused by COVID-19 pandemic on the traditional sources of information, its utilization remains low particularly across many countries. In advanced economies however, as AI gains popularity in banking, financial institutions (FIs) are building on their existing solutions to transform customer experiences to solve increasingly complex challenges and expectations. This paper illustrates the potential of employing AI in banking to reduce costs, including through opportunities it offers to banks to leverage algorithms on the front end to smooth customer identification and authentication, mimic live employees through chatbots and voice assistants, deepen customer relationships, and provide personalized insights and recommendations.Further, AI can also be used by banks within middle-office functions to assess risks, detect and prevent payments fraud, improve processes for anti-money laundering (AML) and perform know-your-customer (KYC) regulatory checks.The main output involves an interactive dashboard illustrating application of the descriptive and predictive analytics at a click for a given business unit of a bank.
Keywords: 330; Künstliche Intelligenz; Betriebliches Informationssystem; Bank; Kenia